Cr(III) dynamic removal in a fixed-bed column by using a co-gasification char - Dias, Diogo (2021)
ABSTRACT: A char (GC) obtained from the co-gasification of rice husk and polyethylene was used in a fixed-bed column with continuous flow for Cr(III) removal assays from synthetic and industrial wastewaters. For comparison purposes, a commercial activated carbon (CAC) was also used. The best experimental conditions in the continuous removal assays were the following ones: Cr(III) inflow concentration = 5 mg L-1, feed flow rate = 3 mL min(-1), mass of adsorbent in the column = 0.8 g, and inflow temperature = 50 degrees C. Under these conditions, the highest uptake capacities were 1.60 and 2.14 mg g(-1) in the synthetic solution, and 3.25 and 7.83 mg g(-1) in the industrial wastewater, for GC and CAC, respectively. These results are different from those obtained under batch conditions in which GC performed better than CAC. Cr(III) removal by both adsorbents occurred due to precipitation, but CAC presented a slightly higher amount of Cr(III) removed due to its highest porosity. The regeneration of GC and CAC was also studied, but both adsorbents showed no capacity to be used in more than one cycle. This study highlighted the importance of studying Cr(III) removal under continuous conditions, as the removal mechanisms may be completely different from the batch assays, affecting the adsorbents' performance.